Identification of Gastrointestinal Endoparasites in Native Chickens (Gallus domesticus) in Pattongko Village, Sinjai Tengah District, Sinjai Regency - Evi Erviani, Andi; Hasyim, Zohra; Musawwir, Saeful (UNIVERSITAS PGRI MADIUN, 2024)
One of the livestock commodities in South Sulawesi is local chicken or native chicken (Gallus domesticus). Although this type of chicken has a high adaptability ability, native chickens can also experience illness and population reduction on farms that can be caused by worm-type endoparasites. This study was conducted from July to August 2023 in Pattongko Village, Central Sinjai District, Sinjai Regency with the aim of finding out what types of endoparasites are found in the gastrointestinal of native chickens in Pattongko Village. Sampling was carried out by random sampling method using 20 native chickens whose feces were taken as much as 5 grams per head. Sample preparation was carried out at the Zoology Laboratory FMIPA Hasanuddin University and sample examination and identification were carried out at the Parasitology Laboratory of the Maros Veterinary Center, which conducts 3 types of sample testing, namely the native method, the flotation method and the sedimentation method. The results of the study found 5 species of gastrointestinal endoparasites belonging to 2 classes, namely the nematode and cestode classes. Parasitic worms belonging to the nematode class are Heterakis spp., Ascaridia spp., Syngamus spp. and Capillaria spp. While parasitic worms belonging to the cestode class are Hymenolepis spp.